2003
DOI: 10.1002/jez.a.10238
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the effects of vasoactive substances on the bulbus arteriosus of the eel, Anguilla rostrata

Abstract: The fish bulbus arteriosus (BA) smoothes cardiac output by expanding during cardiac systole and rebounding during diastole, thereby providing constant perfusion of the gills downstream. Published data have demonstrated innervation of the teleost BA and shown that the tension and compliance of the BA responded to vasoactive agonists, such as epinephrine and acetylcholine, suggesting that the BA was more than a mere ''windkessel.'' To examine vasoactivity in the BA more directly, we measured the responses of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The dogfish shark appears to be unique in that ET-1 stimulation of vascular contraction in dorsal aorta and anterior mesenteric artery (Evans et al, 1996;Evans, 2001), or of increases in [Ca 2+ ]i in anterior mesenteric artery, occurred exclusively via ETBR activation (this study). Evidence for ETBR in teleost fish VSM was demonstrated in the bulbus arteriosus of the eel Anguilla rostrata in studies where there was dose-dependent constriction to ET-1 and SRX (Evans et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The dogfish shark appears to be unique in that ET-1 stimulation of vascular contraction in dorsal aorta and anterior mesenteric artery (Evans et al, 1996;Evans, 2001), or of increases in [Ca 2+ ]i in anterior mesenteric artery, occurred exclusively via ETBR activation (this study). Evidence for ETBR in teleost fish VSM was demonstrated in the bulbus arteriosus of the eel Anguilla rostrata in studies where there was dose-dependent constriction to ET-1 and SRX (Evans et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies testing the effects of vasoactive substances are needed to verify this notion. Characterization of such effects on the teleost bulbus indicates that it is under neurohormonal control (Evans et al. 2003), a fact which denotes that the bulbus is much more than a ‘Windkessel’ (Von Skramlick, 1935), as classically assumed.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in both teleosts and elasmobranchs suggest that the paraphyletic group of fishes relies upon other vasoregulatory mechanisms. These data, mainly derived from ex vivo isolated blood vessels, are often confusing and contradictory (Olson & Villa, 1991; McGeer & Eddy, 1996; Eddy & Tibbs, 2003), but it does appear that NO produces significant dilation of the teleost bulbus arteriosus (Evans et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in the spiny dogfish shark (Squalus acanthias), there is evidence for ET B -like receptors in the gill (6) and aorta (5). In the eel (Anguilla rostrata), pharmacological evidence points toward involvement of an ET B -like receptor in bulbus arteriosus contraction, but the presence of ET A -like receptors could not be ruled out (8). Moreover, Evans and Harrie (7) showed that the ventral aorta of the eel does not respond to the specific ET B receptor agonist SRX S6c.…”
mentioning
confidence: 95%